2018
DOI: 10.1155/2018/1751583
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of a Hydrolyzed Polysaccharide Dietary Supplement on Biomarkers in Adults with Nonalcoholic Fatty Liver Disease

Abstract: The primary objective of the study was to evaluate the effect of a hydrolyzed polysaccharide, Rice Bran Arabinoxylan Compound (RBAC), on biomarkers in adults with nonalcoholic fatty liver disease (NAFLD). A 90-day randomized double-blind placebo-controlled trial examined the effect of RBAC on complete blood count, liver enzymes, lipids, oxidative stress markers, cytokines, and growth factors. Twenty-three adults with NAFLD were enrolled and randomly assigned to one of the two study conditions (n = 12 RBAC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Evidence suggests that some components of seaweeds‐namely, fibre, polyphenol and carotenoids‐may protect against NAFLD 43,44 . Firstly, dietary fibre is the largest component of the seaweed biomass 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that some components of seaweeds‐namely, fibre, polyphenol and carotenoids‐may protect against NAFLD 43,44 . Firstly, dietary fibre is the largest component of the seaweed biomass 45 .…”
Section: Discussionmentioning
confidence: 99%
“…If its efficacy is confirmed, it would suggest a significant health benefit that could be accessed broadly and easily. A group at the University of Miami Miller School of Medicine suggested the effect of a hydrolyzed polysaccharide supplement from rice bran on immunomodulatory biomarkers in adults with nonalcoholic fatty liver disease [24, 25]. A Korean research group suggested that acute grape seed extract can be an effective way to decrease cellular membrane damage after excessive exercise [26].…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in both neutrophils and neutrophil-to-lymphocyte ratio in RBAC group compared to placebo were also observed, even though not statistically significant, may be clinically relevant. No adverse events caused by RBAC was reported in this study [ 82 ]. Overall, the evidence on the beneficial effects of RBAC for managing NAFLD is promising.…”
Section: Clinical Applicationsmentioning
confidence: 97%
“…RBAC supplementation also benefits patients with nonalcoholic fatty liver disease (NAFLD). In a 90-day double-blind, placebo RCT [ 82 ], 23 NAFLD patients were randomly assigned to consume 1 g/day of either RBAC or placebo. Serum biomarkers were assessed at baseline, 45, and 90 days.…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation